1992
DOI: 10.1103/physrevlett.68.911
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast intrinsic optical switching in a dense medium of two-level atoms

Abstract: We performed a numerical investigation of the dynamics of the Bloch equations, extended for dense media (media having many atoms within a cubic resonance wavelength), for optical pulses whose duration is much less than an induced-dipole dephasing time. We find a signature of near dipole-dipole interaction which may provide a useful method for validating the first-principles model, for measuring the strength of the interaction, and for coherent pumping. Further, we demonstrate a new and unique optical switching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
69
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 9 publications
(7 reference statements)
2
69
0
Order By: Relevance
“…Later it was conjectured that local-field corrections alone could give rise to mirrorless OB [9]. This type of bistability was extensively studied [10][11][12][13][14] and observed experimentally [15].The practical interest in all-optical devices faded to some extent as their solid-state counterparts proved to perform better in terms of switching speed and device density. However, OB and optical hysteresis remain of considerable interest from the fundamental standpoint as a clear manifestation of a nonlinear light-matter interaction.…”
mentioning
confidence: 99%
“…Later it was conjectured that local-field corrections alone could give rise to mirrorless OB [9]. This type of bistability was extensively studied [10][11][12][13][14] and observed experimentally [15].The practical interest in all-optical devices faded to some extent as their solid-state counterparts proved to perform better in terms of switching speed and device density. However, OB and optical hysteresis remain of considerable interest from the fundamental standpoint as a clear manifestation of a nonlinear light-matter interaction.…”
mentioning
confidence: 99%
“…Although this approach is not rigorous, it clearly demonstrates that, sufficiently far from the above-mentioned NLS (small-frequency small-amplitude) limit, Bragg-grating solitons can be unstable. Later, a rigorous analysis of the same stability problem was developed by Barashenkov, Pelinovsky and Zemlyanaya [1998] and by de Rossi, Conti and Trillo [1998]. It has been demonstrated that the Bragggrating solitons indeed have instability regions in their parametric (ω, v) plane, which are close to those originally predicted by means of the variational approximation.…”
Section: Introduction § § § Introductionmentioning
confidence: 64%
“…This behavior is more remarkable than the response of conventional two-level systems, because the medium can only be found in one of two states: either fully inverted, or in the ground state, depending (quasi-periodically) on the ratio between the peak fieldstrength and the NDD coupling strength. This feature was found to be impervious to changes in pulse shape, and independent of the pulse area (Crenshaw, Scalora and Bowden [1992]). …”
Section: Sit In Thin Filmsmentioning
confidence: 99%
See 2 more Smart Citations